Nilai Budaya dalam Cerita Rakyat (Seni Barongan) di Kudus - Sunaisah Sunaisah; Iffatul Ulya Rosyadi; Farida Maulida; Mohammad Kanzunnudin (Morfologi : Jurnal Ilmu Pendidikan, Bahasa, Sastra dan Budaya, 2024)
This study aims to analyze the cultural value of the folklore of Barongan Kudus Art. This research was motivated by the lack of public knowledge of the values contained in barongan art. The method used is qualitative descriptive. The source of the data comes from a book entitled "East Coast Folklore" written by Mohammad Kanzunnudin published by CV Adhigama in 2024 page 75. The data is in the form of fragments of the Holy Barongan Art story. Data collection techniques are carried out by the read and listen method. Data analysis techniques using Miles and Huberman's theory are (1) data collection, (2) data presentation, (3) data reduction, (4) verification. The results of the analysis show the values contained in barongan art, namely the value of beauty, biological value, scientific value, skill.